Description of two new Asian Pristaulacus Kieffer 1900 (Hymenoptera: Aulacidae) - Turrisi, Giuseppe Fabrizio; Watanabe, Kyohei (Zootaxa, 2011)
Two Aulacidae from Asia, Pristaulacus japonicus Turrisi & Watanabe, sp.n. (Japan) and Pristaulacus takakuwai Turrisi & Watanabe, sp.n. (Thailand), are described and illustrated. The former species is very similar to the Palearctic Pristaulacus gibbator (Thunberg 1822) and is recognized by the different sculpturing of the upper part of the mesoand metapleura, slightly longer petiole, longer ovipositor, and several features of the male genital capsule, e.g., the shape of the apex of the paramere, lamina volsellaris and penis valve. The latter species is not obviously allied to any other described Oriental Pristaulacus and is recognized by the combination of the following characters: colour pattern, with setae of the body golden, wings yellowish hyaline, fore wing with a moderately wide substigmal brown spot and apex infuscated, hind leg mostly black to black-brown, shape of the head, with temple well developed, and ovipositor relatively short, 0.9× fore wing length. Images of both treated species are freely available at the web site: http://morphbank.net.